Bridging the Gap in Interactive Education: A WordWall Training Initiative for MGMP Instructors in Padang Panjang - Agustina, Dina (Fakultas MIPA Universitas Negeri Padang, 2024)
In the quest for educational advancement in Padang Panjang, Indonesia, this article presents a groundbreaking initiative titled